Information technology in developing countries: proceedings... - Bhatnagar, Subhash C. ed. (North-Holland AmsterdamNL, 1990)
Discusses a theoretical framework for developing and implementing information systems in a developing country context. Presents country reports covering many aspects of computerisation in these countries. Presents a regional/comparative status of computer use in selected countries.